2019
DOI: 10.1177/0309133319841891
|View full text |Cite
|
Sign up to set email alerts
|

Trends in evapotranspiration and its drivers in Great Britain: 1961 to 2015

Abstract: In a warming climate, the water budget of the land is subject to varying forces such as increasing evaporative demand, mainly through the increased temperature, and changes to the precipitation, which might go up or down. Using a verified, physically based model with 55 years of observation-based meteorological forcing, an analysis of the water budget demonstrates that Great Britain is getting warmer and wetter. Increases in precipitation (2.96.0 ± 2.03 mm yr–1 yr–1) and air temperature (0.20 ± 0.13 K decade–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…Trend analysis is an effective method to detect changes in climatic and hydrological variables [14,16,20,26,55,[59][60][61]. e Mann-Kendall test has been widely used to detect trends in reference evapotranspiration, streamflow, temperature, and precipitation time series in different regions around the world [14,15,23,24,47,[62][63][64][65]. In this study, a modified Mann-Kendall trend test was used to detect the change in streamflow, rainfall, and average temperature.…”
Section: Evaluation Of Homogeneity Testsmentioning
confidence: 99%
“…Trend analysis is an effective method to detect changes in climatic and hydrological variables [14,16,20,26,55,[59][60][61]. e Mann-Kendall test has been widely used to detect trends in reference evapotranspiration, streamflow, temperature, and precipitation time series in different regions around the world [14,15,23,24,47,[62][63][64][65]. In this study, a modified Mann-Kendall trend test was used to detect the change in streamflow, rainfall, and average temperature.…”
Section: Evaluation Of Homogeneity Testsmentioning
confidence: 99%
“…With the emergence of new digital technologies and increased monitoring of the earth system via satellites and sensors, we now have greater access to data than ever before. This prolifera-tion of data has been reflected in recent projects where there has been a focus on sharing data and collaborative research (SWITCH-ON; Ceola et al, 2015), collecting new datasets through the creation of terrestrial environmental observatories (TERENO; Zacharias et al, 2011) or the Critical Zone Observatories (CZOs; Brantley et al, 2017), and cloud-based resources for modelling and visualising large datasets such as the Environmental Virtual Observatory (EVO; Emmett et al, 2014) and the CUAHSI HydroDesktop (Ames et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In common with the evolution of other land surface models (Blyth et al, 2021;Clark et al, 2015), JULES is increasingly being applied and assessed with a view to have a more complete representation of terrestrial hydrology in addition to continuing focus on the representation of land-atmosphere coupling as has been more traditional in their use as an interacting lower boundary for weather and climate prediction. It has been previously demonstrated that JULES can provide accurate daily river flow simulations over selected catchments in Great Britain when driven by observation-based meteorological forcing (Martinez-de la Torre et al, 2019), while G omez et al (2020 demonstrated good river flow predictions when driven by an operational JULES-based regional land surface analysis. There are however known deficiencies in the hydrological performance of JULES over the UK, including excessive evaporation rates (Blyth et al, 2019), insufficient infiltration (Largeron et al, 2018) and numerous inherent parameterisation and parameter uncertainties (Martinezde la .…”
Section: Introductionmentioning
confidence: 99%